PENGARUH SARAPAN PAGI TERHADAP KONSENTRASI BELAJAR SISWA KELAS V DI SDS TARBIYATUL ISLAM SAMBAS TAHUN PELAJARAN 2023-2024 - Klania Istiqomah; Parni, Astaman (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This journal aims to obtain complete and in-depth information about breakfast and concentration and the influence that exists between breakfast and student learning concentration at SDS Tarbiyatul Islam Sambas for the 2023-2024 academic year. The research approach used is quantitative with an associative type of research.The population is 28 people. The data analysis technique uses Pearson product moment correlation and simple linear regression, with the research results being that variable X breakfast is in the "Good" category seen from the percentage results, namely 7.151%. Meanwhile, variable Y, namely student learning concentration, is in the "Very Good” category from the percentage results, namely 83.48%. There is a significant influence between breakfast on the learning concentration of class V students at SDS Tarbiyatul Islam Sambas. This can be seen from the relationship between the two variables with a correlation of 0.411, located between 0.400-0.599, which is included in the medium category, with a significance level of 0.016 < 0.05, thus (Ha) is accepted and (HO) is rejected. Seeing from the calculation results that the result a is 50.239 and b is 0.467, it is found that the regression equation for breakfast and study concentration is: Y= 50.239 + 0.467X. From the equation above, it means that every increase in variable X by one unit will be followed by an increase in variable Y of 0.467 with the price a = constant. In other words, the magnitude of the influence of variable X on the increase in variable Y is 0.467.